PENERAPAN MODEL PEMBELAJARAN BERMAIN PERAN (ROLE PLAYING) UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL - Sastra Wijaya (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
APPLICATION OF THE ROLE TO PLAY LEARNING MODEL TO IMPROVE RESULTS LEARN IN LESSONS SOCIAL SCIENCESApplication of Role Play Learning Model to Improve Learning Outcomes in Social Science Learning (This Study with Classroom Action Research Approach for Class IV Students of State Elementary School 1 Walantaka Walantaka District Serang City 2017/2018 Academic Year). This research is a Classroom Action Research (CAR). From the results of observations of the cycle I data on student learning outcomes in learning, teachers only get a score of 61.3. Students have started to be active, this is evidenced by the results of student observations that have reached 61.3. Then from the results of student learning in the first cycle of Meeting 1 obtained data, student learning completeness only reached 45.83 with an average value of 54.17. From the data of student learning outcomes in the first cycle of meeting 2 results of learning observation, the teacher gets a score of 74.9. students have started active, this is evidenced by the results of student observations that have reached 74.9. Then from the results of student learning in the first cycle of Meeting 2 obtained data, student learning completeness only reached 70.83 with an average value of 67.35. From the data of student learning outcomes in cycle II learning observation results, the teacher gets a score of 86.4., Students have begun to be active, this is evidenced by the results of student observations that have reached 88.89 Then from student learning outcomes in cycle II obtained data, student learning completeness reaches 100% with an average value of 77.39. Based on the above data it is concluded that the application of role playing learning models can improve learning outcomes in social studies lessons at SD Negeri 1 Walantaka, Walantaka District, Serang City in 2017/2018.